2014
DOI: 10.1177/1098214014538487
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of the “Counterfactual as Self-Estimated by Program Participants”

Abstract: In this article, we test an alternative approach to creating a counterfactual basis for estimating individual and average treatment effects. Instead of using control/comparison groups or before-measures, the so-called Counterfactual as Self-Estimated by Program Participants (CSEPP) relies on program participants' self-estimations of their own counterfactual at the end of an intervention. In an empirical study, a randomized experiment was employed as a benchmark to examine the performance of the CSEPP. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 23 publications
(27 reference statements)
1
33
1
Order By: Relevance
“…However as stated in the Methods, a number of studies from various disciplines have established that self‐report data, although not perfect are actually reasonable surrogates for more direct measures, especially when using survey data (Chan, ; Gonyea, ; Vaske, ). Similar challenges arise due to the use of retrospective data as a surrogate for actual early adolescent experiences, although as above, several investigators have found such approaches yield quite acceptable results (Lam & Bengo, ; Mueller & Gaus, ; Schwarz, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However as stated in the Methods, a number of studies from various disciplines have established that self‐report data, although not perfect are actually reasonable surrogates for more direct measures, especially when using survey data (Chan, ; Gonyea, ; Vaske, ). Similar challenges arise due to the use of retrospective data as a surrogate for actual early adolescent experiences, although as above, several investigators have found such approaches yield quite acceptable results (Lam & Bengo, ; Mueller & Gaus, ; Schwarz, ).…”
Section: Discussionmentioning
confidence: 92%
“…However as documented by a number of studies from various disciplines, self‐reports are actually reasonable surrogates for more direct measures, especially when using survey data (Chan, ; Gonyea, ; Vaske, ). The same is true for retrospective self‐reports (Lam & Bengo, ; Mueller & Gaus, ; Schwarz, ), particularly given how challenging information about past events can be to collect.…”
Section: Methodsmentioning
confidence: 97%
“…This approach provides some information about possible program effects, but does not solve the second limitation, the lack of a comparison (also known as counterfactual) condition. Specifically, evaluators may not have access to individuals or groups who did not (Mueller & Gaus, 2015).…”
Section: Retrospective Assessments Of Program Effectsmentioning
confidence: 99%
“…Many sources of existing data can support a sunset evaluation, and some can even allow for the use of a number of traditional evaluation designs (Shadish, Cook, & Campbell, 2002 (Mueller & Gaus, 2015).…”
Section: Leveraging Existing Datamentioning
confidence: 99%